Growth differentiation factor 15 protects against the aging‐mediated systemic inflammatory response in humans and mice - Moon, Ji Sun; Goeminne, Ludger J. E.; Kim, Jung Tae; Tian, Jing Wen; Kim, Seok‐Hwan; Nga, Ha Thi; Kang, Seul Gi; Kang, Baeki E.; Byun, Jin‐Seok; Lee, Young‐Sun; Jeon, Jae‐Han; Shong, Minho; et al. (Aging cell, 2020)
Mitochondrial dysfunction is associated with aging‐mediated inflammatory responses, leading to metabolic deterioration, development of insulin resistance, and type 2 diabetes. Growth differentiation factor 15 (GDF15) is an important mitokine generated in response to mitochondrial stress and dysfunction; however, the implications of GDF15 to the aging process are poorly understood in mammals. In this study, we identified a link between mitochondrial stress‐induced GDF15 production and protection from tissue inflammation on aging in humans and mice. We observed an increase in serum levels and hepatic expression of GDF15 as well as pro‐inflammatory cytokines in elderly subjects. Circulating levels of cell‐free mitochondrial DNA were significantly higher in elderly subjects with elevated serum levels of GDF15. In the BXD mouse reference population, mice with metabolic impairments and shorter survival were found to exhibit higher hepatic Gdf15 expression. Mendelian randomization links reduced GDF15 expression in human blood to increased body weight and inflammation. GDF15 deficiency promotes tissue inflammation by increasing the activation of resident immune cells in metabolic organs, such as in the liver and adipose tissues of 20‐month‐old mice. Aging also results in more severe liver injury and hepatic fat deposition in Gdf15‐deficient mice. Although GDF15 is not required for Th17 cell differentiation and IL‐17 production in Th17 cells, GDF15 contributes to regulatory T‐cell‐mediated suppression of conventional T‐cell activation and inflammatory cytokines. Taken together, these data reveal that GDF15 is indispensable for attenuating aging‐mediated local and systemic inflammation, thereby maintaining glucose homeostasis and insulin sensitivity in humans and mice. Aging‐induced GDF15 production is observed in humans and mice, which is positively correlated with systemic inflammation and mitochondrial stress. GDF15 deficiency promotes glucose intolerance as well as hepatic and adipose inflammation in old mice. GDF15 contributes to regulatory T cells‐mediated suppression of conventional T cell activation, but senescent T cells were resistant to regulatory T cells‐mediated suppression compared to conventional T cells.